Bagaimana Menulis Biografi Audiovisual Poststrukturalis? - I Nyoman Wijaya (Jurnal Sejarah Citra Lekha, 2021)
Poststructuralist audiovisual biography is written using a poststructuralist historical approach and audiovisual archives. This study presents a new method in writing concise and concise biographies for the purpose of making papers and publication articles. The problem is focused on how the writing technique is? Like poststructuralist history, this biography model departs from the actor's present situation in the past. The goal is to explore the actor’s experience that brought him to where he is now. The actor’s successness or failureness today depend on the capital (resources) he has. Are these resources in accordance with the profession? Resources are formed from habits that have undergone internalization to form habits as a guide for actors in thinking and acting when dealing with social reality. Considering this biography model is relatively unknown to academics and history students in genera. This study also discusses the method to write biography as well as the theory that can be used as a basis for thinking. Thus, Bourdieu's generative structural theory is considered very relevant to be used.